Large-Sided Games and Sport-Specific Training: Parameters of High Intensity in Professional Soccer Players - Sannicandro, Italo; Cofano, Giacomo (Physical Education Theory and Methodology, 2023)
Study purpose. This study aimed to describe, analyze and compare the high intensity in internal and external load deriving from Large-Sided Games (LSG) exercises during the 4vs4 and 5vs5 formats, with goalkeepers. Materials and methods. The study participants were 22 professional soccer players (average age: 23.59±4.87 years, weight: 77.8±7.6 kg; height: 183.5±7.5 cm). The 4vs4 + 2 goalkeepers format was performed on a 60x54 m field (324 m2per player), while the 5vs5 + 2 goalkeepers format was performed on a 65 x 60 m field (325 m2 per player). During the two LSG exercises, the internal load and the external load were analyzed. The LSG exercises were performed in 4 sets of 5 minutes each, with 2 minutes of passive recovery between each set. Results. The data obtained show that the 4vs4 is the LSG exercise that succeeds in ensuring high exercise intensity: the time spent between 90-100% of the Heart Rate (HR) is significantly higher than in the 5vs5 (p <.005). The average HR values (percentage and absolute) were also higher and significant (p <.05) in the 4vs4 LSG. The peak speed (p < .05), average metabolic power during exercise phases (p < .05) and sprint distance (p < .005) are higher in the 5vs5 LSG. Conclusions. By modulating the practice time, both formats can be used on the day after the match for those who did not play or on the match-day +3 for the whole team.